Características epidemiológicas e ambientais relacionadas a dengue em duas maiores cidades do Estado do Tocantins em um período de onze anos (2000 a 2010). - Valadares, Adriane Feitosa (2012)
Dengue is a growing public health issue worldwide. As a result of their environmental, climatic and social characteristics, tropical countries are those most affected. The objectives of the present study conducted in the state of Tocantins, Brazil, were: to identify the demographic characteristics of notified and confirmed cases of dengue; to calculate the incidence rate of confirmed cases of dengue; to investigate the correlation between confirmed cases and the number of hospitalizations for this disease; to correlate the number of hospitalizations and the number of severe cases; to describe the circulating serotypes identified; to investigate the correlation between the house infestation index and the incidence rate of dengue; and to investigate the correlation between environmental factors such as mean annual temperature and mean rainfall with the annual incidence rate of dengue. This was an ecological, longitudinal study conducted by evaluating secondary data for the 2000- 2010 period obtained from the Brazilian Ministry of Health s notifiable diseases database, the yellow fever and dengue database, the localities database, the hospital admissions database and from the dengue and yellow fever management unit of the Tocantins State Health Department. The mean temperatures in degrees Celsius and the mean rainfall in millimeters were supplied by the National Meteorology Institute. The data on viral isolation and serotyping were obtained from the Tocantins Central Public Health Laboratory. The inclusion criterion adopted in this study consisted of municipalities in the state of Tocantins with populations of more than 100,000 inhabitants in this case, Palmas and Araguaína. A total of 48,246 suspected cases of dengue were notified during the period and 23,614 (49%) were confirmed. Of these, 118 (0.5%) were classified as severe cases and 7 deaths occurred (5.9%). The highest prevalence of the disease occurred in females (52.9%), in individuals of 20-39 years of age (46.5%), in those living in urban areas (97.6%) and in brown-skinned individuals (51.5%). There was a statistically significant difference (p<0.05) between the variables evaluated. The highest incidence of dengue occurred in 2007; however, the greatest number of severe cases registered was in 2008, although no deaths were recorded. Of the hospitalized patients, 13% were classified as severe cases. There was a positive and significant correlation between the number of confirmed cases and the number of hospitalizations (r = 0.77; p < 0.05), as well as between hospitalizations and severe cases (r = 0.79; p < 0.05). The serotypes isolated were DENV 1, DENV 2 and DENV 3. There was a positive, albeit non-significant, correlation between the house infestation index and the incidence of the disease (r = 0.59; p > 0.05). With respect to the abiotic factors, no correlation was found between mean rainfall or mean annual temperature and the incidence rate. In conclusion, the highest incidence of dengue occurred in 2007 and the greatest number of severe cases occurred in 2008, albeit with no deaths. These findings indicate that dengue affects predominantly females, individuals of 20-39 years of age, brown-skinned individuals and those residing in urban areas. The correlation between confirmed cases and hospitalizations was significant, as was the correlation between hospitalizations and severe cases of dengue. The serotypes identified were DENV 1, DENV 2 and DENV 3. More than one serotype was circulating simultaneously. The correlations between mean rainfall and the incidence rate and between mean temperature and the incidence rate were not statistically significant.